Depressive symptoms and comorbid problems in pregnancy - results from a population based study - Pampaka, Despina; Papatheodorou, Stefania; AlSeaidan, Mohammad; Al Wotayan, Rihab; Wright, Rosalind John; Buring, Julie E; Dockery, Douglas W.; Christophi, Costas A. (My University, 2018)
Objective To estimate the prevalence of antenatal depressive symptoms, identify relevant risk factors, and assess comorbid mental health problems, among pregnant women enrolled in a population based study. Methods This was a secondary analysis of data collected from 1916 pregnant women who participated in the TRansgenerational Assessment of Children's Environmental Risk (TRACER) study in Kuwait, and had answered the Baseline Questionnaire and completed the Edinburgh Depression Scale (EDS). Logistic regression models were used to examine the association of depressive symptoms with baseline socio-demographic characteristics and psychosocial indicators. Results The prevalence of antenatal depressive symptoms, using a cut-off of EDS score ≥ 10, was 20.1%. Depressive symptoms were reported more by women of lower family income and had self-reported history of depression prior to pregnancy, with women in the third trimester having higher odds of antenatal depressive symptoms compared to those in the second trimester. Pregnancy-related anxiety, higher perceived stress levels, and post-traumatic stress disorder symptoms were comorbid with the presence of depressive symptoms. Conclusion The findings showed that one in five pregnant women in Kuwait experiences antenatal depressive symptoms and that these symptoms are comorbid with other mental health problems. Screening for antenatal depression and providing support to pregnant women should be considered.
Keywords: Antenatal; Depressive symptoms; Kuwait; Mental health; Pregnancy